Postoperative Assessment of Extracranial–Intracranial Bypass by Time-Resolved 3D Contrast-Enhanced MR Angiography Using Parallel Imaging - Tsuchiya, Kazuhiro; Honya, Keita; Fujikawa, Akira; Tateishi, Hidekatsu; Shiokawa, Yoshiaki (American Journal of Neuroradiology, 2005)
PURPOSE: Our goals were to assess image quality of time-resolved contrast-enhanced MR angiography (CE MRA), by using 3D data acquisition along with a parallel imaging technique that can improve temporal resolution and to compare this technique with 3D-time-of-flight (TOF) MRA in the postoperative assessment of extracranial (EC)–intracranial (IC) bypass surgery.METHODS: On a 1.5T imaging system, we performed CE MRA by using a 3D fast field-echo sequence in combination with a parallel imaging technique, to obtain images in the coronal plane centered at the postoperative site. Our patient group comprised 17 patients, including 13 after superficial temporal artery–middle cerebral artery (MCA) anastomosis, 3 after external carotid artery-MCA anastomosis, and one after extracranial vertebral artery–posterior cerebral artery anastomosis. Visualization of the anastomosis and the distal flow on the CE-MRA images was assessed comparatively with that on 3D-TOF MR angiograms obtained at the same time. In 6 patients, we also compared the efficiency of visualization on CE-MRA images with that on conventional angiograms.RESULTS: A temporal resolution of 0.8 s/frame could be achieved with the technique employed. The bypass was better demonstrated postoperatively on CE-MRA images than on 3D-TOF MR angiograms in 13 patients (76%), whereas the 2 methods were equivalent in 4 patients (24%). Good correspondence of results was observed in the 6 patients for whom CE MRA and conventional digital subtraction angiography (DSA) images were compared.CONCLUSION: CE MRA by using the parallel imaging technique can increase image acquisition speed with sufficient image quality. This technique is at least equivalent to 3D-TOF MRA to evaluate the postoperative status of EC-IC bypass.